2016
DOI: 10.1007/s00216-016-9554-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dots-decorated multiwalled carbon nanotubes nanocomposites as a high-performance electrochemical sensor for detection of H2O2 in living cells

Abstract: A novel enzyme-free hydrogen peroxide sensor composed of carbon dots (CDs) and multi-walled carbon nanotubes (MWCNTs) was prepared. It was found that the carbon dots-decorated multi-walled carbon nanotubes nanocomposites (CDs/MWCNTs) modified glassy carbon (GC) electrode (CDs/MWCNTs/GCE) exhibited a significant synergistic electrocatalytic activity towards hydrogen peroxide reduction as compared to carbon dots or multi-walled carbon nanotubes alone, and the CDs/MWCNTs/GCE has shown a low detection limit as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…A moderate sensitivity of 0.13 mV/μM is obtained from a linear range of 1 to 200 μM whereas it is 82 mV/μM from a linear range of 0.5 to 1 μM. Our detection limit of 1 μM is inferior than the published results [ 9 12 , 15 , 16 , 41 43 ], comparable with the published results [ 44 47 ], and superior than the published results [ 13 , 17 , 18 , 20 , 48 52 ] in literature by using different sensing methods, as shown in Table 1 . Further study is needed to improve the detection limit in the future.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…A moderate sensitivity of 0.13 mV/μM is obtained from a linear range of 1 to 200 μM whereas it is 82 mV/μM from a linear range of 0.5 to 1 μM. Our detection limit of 1 μM is inferior than the published results [ 9 12 , 15 , 16 , 41 43 ], comparable with the published results [ 44 47 ], and superior than the published results [ 13 , 17 , 18 , 20 , 48 52 ] in literature by using different sensing methods, as shown in Table 1 . Further study is needed to improve the detection limit in the future.…”
Section: Resultssupporting
confidence: 55%
“…Hao et al [ 19 ] have developed an amperometric H 2 O 2 sensor based on Fe 2 O 3 nanoparticles. Bai et al [ 20 ] have reported a sensor based on carbon dot-decorated multi-walled carbon nano-composites. Silver (Ag) nanowire [ 21 ] and nanoparticle-decorated graphene [ 22 ] have been also reported for H 2 O 2 sensing.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that the proposed electrode shows high electrocatalytic activity toward H 2 O 2 released from prostate cancer cell (PC‐3) versus non‐cancerous cell (BPH‐1) therefore facilitating the detectability of peroxide [48] . Furthermore, CDs/MWCNTs/GCE displayed a novel electrocatalytic activity towards H 2 O 2 reduction [49] …”
Section: Electrochemical Carbon Nanodot‐based Sensors and Biosensorsmentioning
confidence: 99%
“…9 Horseradish peroxidase (HRP) and catalase (CAT) are the two kinds of enzymes that are commonly used for H 2 O 2 detection. However, the immobilization and stabilization protocol of the enzyme are complicated, and it is difficult to achieve the direct electron transfer on bare electrode.…”
Section: Enzyme-based Biosensormentioning
confidence: 99%